THE PRESENCE OF MULTI-FAITH ARCHITECTURE: A CASE STUDY OF CALVARY CHURCH AND CALVARY CHURCH CONVENTION CENTRE TO CREATE A LESS ISOLATIONIST IMAGE IN A MULTIFAITH COMMUNITY - Tan Han Leong; Intan Liana Samsudin; Nor Syawallina Azman; Mohd. Tajuddin Mohd. Rasdi (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The purpose of this study is to outline the design elements of church architecture and activities towards encouraging a less isolationist image within a multifaith community. The research case studies include Calvary Church (CC) and Calvary Convention Centre (CCC). Qualitative case studies through observations and interviews are conducted to get information on perceptions of the architectural spaces, programs, and design elements applied to the case studies. The data analysis approach used is content analysis and descriptive analysis for both case studies, creating a less isolationist image and encouraging the multifaith community urban context. The results revealed that intimacy, proximity, neutrality, universal character, and flexibility are essential for creating a positive shared space design for a church building.